Pengaruh Faktor Daya Tarik Ekowisata terhadap Keputusan Berkunjung Wisatawan di Kawasan Mangrove Karangsong Kabupaten Indramayu - Istiqomah; Fitri Rahmafitria; Reiza Miftah Wirakusuma (Media Wisata, 2022)
This study aims to analyze the effect of eco-tourism attraction on the decision to visit tourists in the Ecotourism Mangrove Area of Karangsong Indramayu. The research method used is a descriptive research method with a quantitative approach. The results of this study indicate that there is a partial and significant influence between Mangrove Physical Products, Mangrove Activities, Mangrove Facilities and Services on the decision to visit tourists in the Ecotourism Mangrove Area of Karangsong Indramayu. Then for ecotourism attractiveness factors consisting of Mangrove Physical Products, Mangrove Activities, Mangrove Facilities and Services simultaneously significantly influence the decision to visit tourists in the Ecotourism Mangrove Area of Karangsong Indramayu, which is 51.9%. This research can provide additional references and can also assist the management in developing mangrove ecotourism areas to attract more tourists.